Speech of Deputy Minister of Education Y B Encik Chan Siang Sun at the 19th session of the General Conference of Unesco, Nairobi, Kenya on 3rd November, 1976/Chan Siang Sun - 423021 Chan, Siang Sun (Kuala Lumpur, 1976)
44